Cadmium Toxicity on Chondrocytes and the Palliative Effects of 1α, 25-Dihydroxy Vitamin D3 in White Leghorns Chicken's Embryo - Gu, Jianhong; Li, Saihui; Wang, Guoshuai; Zhang, Xueqing; Yuan, Yan; Liu, Xuezhong; Bian, Jianchun; Tong, Xishuai; Liu, Zongping (Frontiers in Veterinary Science, 2021)
Cadmium (Cd) can causes osteoporosis and joint swelling. However, the mechanism of Cd toxicity in chondrocytes and how to alleviate Cd poisoning to chondrocytes are still unclear. Herein, we evaluated the toxicity of Cd to chicken chondrocytes, and whether vitamin D can relieve the toxicity of Cd to chondrocytes. Primary chondrocytes were collected from knee-joint cartilage of 15-day-old chicken embryos. They were treated with (0, 1, 2, and 4) μM Cd alone, 10−8 M 1α,25-(OH)2D3 alone, or 2 μM Cd combined with 10−8 M 1α,25-(OH)2D3. We found that Cd significantly inhibited Sox9 and ACAN mRNA expression, which are markers for chondrocyte differentiation, downregulated the mitochondrial membrane potential, upregulated the Bax/B-cell lymphoma 2 ratio. Furthermore, Cd significantly promoted matrix metalloproteinase (MMP)-9 expression, thus accelerating the degradation of extracellular matrix. And Cd also inhibited the expression of main macromolecular protein of extracellular matrix, Collagen type IIα1 (COL2A1) and acid mucopolysaccharide. However, 1α,25-(OH)2D3 pretreatment significantly alleviated the toxicity effects of Cd on the differentiation, apoptosis and extracellular matrix gene expression in primary chondrocytes. Conclusively, Cd exposure could inhibited chicken embryo chondrocytes differentiation, extracellular matrix gene expression, and induced chondrocyte apoptosis. However, these toxic effects of Cd are alleviated by the pretreatment of chondrocytes with 1α,25-(OH)2D3.